Motivations to Engage in Social Distancing and Depression, Anxiety, and Stress Among Adolescents During COVID-19 Pandemic - Shrestha, Satya B; Bhandari, Menuka; Rai, Munawatee; Khadgi, Karishma (Journal of Institute of Medicine Nepal, 2022)
Introduction The coronavirus disease 2019 (COVID-19) is a pandemic prevalent in most countries globally affecting people of all ages including adolescents. Social distancing was implemented to minimize the spread of the virus. The present study is aimed to determine the factors that motivate adolescents to engage in social distancing and find out the depression, anxiety and stress status of the adolescents during covid-19 pandemic. Methods A quantitative, descriptive cross-sectional study was conducted among 256 adolescents studying in classes 11 and 12 of four 10+2 schools in Biratnagar Metropolitan City. The study duration of this study was 6 months. A complete enumerative sampling technique was used to enroll students. Data was collected by the structured questionnaires containing sociodemographic variables and the Nepali version of the Depression Anxiety Stress 21-point Scale through an online google docs questionnaire. Results The maximum number of respondents (61.8%) maintained a social distance of their own will, and 48.2% of respondents maintained social distance because of external factors. The Prevalence of Depression was 27.8%., Anxiety was 18.5% and Stress was 13.3%. No association was found between social distancing and the mental health of adolescents with demographic variables. Conclusion The present study concluded that adolescents are self-motivated to comply with social distancing rules and there is no effect on their mental health status during the period of the covid-19 pandemic.